What is Full Employment? A Historical-Institutional Analysis of a Changing Concept and Its Policy Relevance for the Twenty-First Century Post-COVID-19 Economies. Issue 2 (3rd April 2021) - Seccareccia, Mario
Abstract: Unemployment and the related concept of full employment have acquired different meaning depending on the historical evolution of capitalist economies since the eighteenth century. The purpose of this article is to provide a broad historical perspective and to contextualize the meaning of full employment in a COVID-19 world and possible aftermath. In opposition to the view of many economists and policy makers on both the Right and Left of the political spectrum, the article affirms that a full-employment policy is not passé. What we have learned from the COVID-19 crisis is that a full-employment commitment ought to be coupled with a "full" or universal basic income system. These should be viewed as complementary and not competing policy visions for a twenty-first-century post-COVID-19 world.